2019
DOI: 10.1371/journal.pone.0223222
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with muscle mass in community-dwelling older people in Singapore: Findings from the SHIELD study

Abstract: ObjectivesAging is associated with low muscle mass and has been linked to adverse health outcomes. The objectives of this cross-sectional study were: (1) to describe anthropometry, body composition, appendicular skeletal muscle mass index (ASMI; appendicular skeletal muscle mass/height2), and prevalence of low ASMI in older people with normal nutritional status (Malnutrition Universal Screening Tool score = 0); (2) to determine factors associated with ASMI, and odds ratios of having low ASMI.MethodsSHIELD is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 90 publications
3
29
1
Order By: Relevance
“…Previous studies that examined human cadavers, such as the study involving male cadavers (n = 12) in Brussels 18 and the study involving white cadavers (n = 23), 19 reported that the maximal calf circumference was positively correlated with total dissected muscle mass (r = 0.84, or men: r = 0.90 and women: r = 0.77). Furthermore, maximal calf circumference was strongly correlated with calf muscle mass measured by magnetic resonance imaging (men: 20 Calf circumference was positively correlated with muscle mass measured by BIA [21][22][23] or DXA [7][8][9][10][11] (BIA-measured ASM: r = 0.68, BIA-measured ASM/height 2 : r = 0.56-0.78, DXA-measured ASM: r = 0.55-0.81, DXAmeasured ASM/height 2 : r = 0.42-0.84). Moreover, the National Health and Nutrition Examination Survey that examined 15 293 participants reported a moderate correlation between calf circumference and DXA-measured ASM across all BMI subgroups (<18.5, 18.5-24.9, 25-29.9, ≥30 kg/m 2 ) or age subgroups (<20, 20-39, 40-59, ≥60 years).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies that examined human cadavers, such as the study involving male cadavers (n = 12) in Brussels 18 and the study involving white cadavers (n = 23), 19 reported that the maximal calf circumference was positively correlated with total dissected muscle mass (r = 0.84, or men: r = 0.90 and women: r = 0.77). Furthermore, maximal calf circumference was strongly correlated with calf muscle mass measured by magnetic resonance imaging (men: 20 Calf circumference was positively correlated with muscle mass measured by BIA [21][22][23] or DXA [7][8][9][10][11] (BIA-measured ASM: r = 0.68, BIA-measured ASM/height 2 : r = 0.56-0.78, DXA-measured ASM: r = 0.55-0.81, DXAmeasured ASM/height 2 : r = 0.42-0.84). Moreover, the National Health and Nutrition Examination Survey that examined 15 293 participants reported a moderate correlation between calf circumference and DXA-measured ASM across all BMI subgroups (<18.5, 18.5-24.9, 25-29.9, ≥30 kg/m 2 ) or age subgroups (<20, 20-39, 40-59, ≥60 years).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, maximal calf circumference was strongly correlated with calf muscle mass measured by magnetic resonance imaging (men: r = 0.91, women: r = 0.89) 20 . Calf circumference was positively correlated with muscle mass measured by BIA 21–23 or DXA 7–11 (BIA‐measured ASM: r = 0.68, BIA‐measured ASM/height 2 : r = 0.56–0.78, DXA‐measured ASM: r = 0.55–0.81, DXA‐measured ASM/height 2 : r = 0.42–0.84). Moreover, the National Health and Nutrition Examination Survey that examined 15 293 participants reported a moderate correlation between calf circumference and DXA‐measured ASM across all BMI subgroups (<18.5, 18.5–24.9, 25–29.9, ≥30 kg/m 2 ) or age subgroups (<20, 20–39, 40–59, ≥60 years) 12 .…”
Section: Discussionmentioning
confidence: 98%
“…The reasons for this are considered as follows. Tey et al reported that the average BMI of patients with low skeletal muscle index was 21.97 kg/m 2 , which was significantly lower than that of patients with normal SMI in elderly populations 35) . Besides, patients with low lean body mass may therefore be exposed to higher concentrations of cytotoxic drugs than those with a higher lean body mass in patients with diffuse ML treated with chemotherapy 36) .…”
Section: Discussionmentioning
confidence: 97%
“…These recommendations were developed by a multidisciplinary working group of eight senior clinicians and researchers in geriatrics, dietetics, gerontology, intensive care medicine, family medicine, physiotherapy and rehabilitation medicine to encompass the entire continuum of care. STH Chew is a Senior Consultant Geriatrician and the Principal Investigator for the SHIELD study [17,18] The panel convened at a face-to-face meeting in Singapore in late-April 2019 to review and discuss available evidence, share clinical practice experience on the management of muscle health and forge a way forward on how best to apply the current evidence and guidelines in clinical settings. We defined the clinical problem as the following: "In light of the rapidly ageing population in Singapore and Asia, what are the best evidencebased interventions available to optimise muscle health in older adults >65 years old that can be delivered by a multidisciplinary team across the continuum of care?…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these subjects with sarcopenia were found to have lower total energy intake and energy-adjusted protein intake based on 24-h dietary recall [ 17 ]. This study also reported a prevalence of 81.3% for low appendicular skeletal mass index (ASMI) based on the AWGS 2014 cut-offs [ 17 ], a striking four-fold increase compared with a nourished cohort with similar baseline characteristics where the prevalence for low ASMI was only 20.6% [ 18 ]. These findings are concerning as one in two Singaporeans aged > 65 years is expected to become severely disabled and require long-term care in their lifetime [ 19 ].…”
Section: Introductionmentioning
confidence: 99%